scholastic biography: hellen keller - Davidson, Margaret; Marget Davidson (New York Scholastic, Inc., 1969)
How does a blind boy or girl read a book? Hellen keller fisrt learned to read by feeling raised letters with her finger tips. Later she learned the special raised dot alphabet called braille.
English